Seismogeological and Geotehnical Conditions of Building in Upper Soča Territory, Slovenia - Ribičič, Mihael; Vidrih, Renato; Godec, Matjaž (Geologija, 2000)
After the earthquake struck the upper Soča territory on April 12th 1998, many studies and analyses have been made on the earthquake’s impacts with the purpose of collecting information leading to a better understanding of seismicity, the best ways of strenghtening buildings and other constructions so as to make them largely earthquake resistant. In pursuing these aims it is necessary for the seismological, geological and civil engineering Sciences to work together. Most damage occurring to buildings caused by the earthquake on April 12th 1998 was suffered by older buildings. In assessing the earthquake’s effects on buildings, the Geophysical Survey of Slovenia and the Civil Engineering Institute ZRMK used the information we collected, as well as information gathered by the building damage assessors who work within the Ministry of Environment and Spatial Planning. The methodology of assessing the damage is in line with the prescribed instructions meaning that all information can be used in assessing the earthquake’s effects in accordance with the instructions of the EMS (European Macroseismic Scale). Apart from analysing building damage, we also prepared a map of the seismic micro-zonation of Posočje, which enables civil engineers to take into account, when strenghtening the damaged buildings and constructing new ones, the expected basic level of seismicity with the probability of an earthquake with a return period of 500 years and the local ground structure. On the basis of the geological and seismological studies, we have assessed the general engineering-geological and geotechnical conditions for new constructions and presented them on various maps and in the detailed descriptions found in the legends to those maps.